INNOVATION OF AIRPORTS AND AERODROMES IN TRANSPORT - Tomasz BALCERZAK; Radosław FELLNER (Scientific Journal of Silesian University of Technology. Series Transport, 2016)
The paper attempts to characterize changes occurring in EU transport policy, taking into account innovation of airports and aerodromes. To face challenges like: increase in air traffic, ensuring safety of flight operations, regional development or requirements of passengers it is necessary to determine desired direction network of airports and aerodromes within the aviation policy, which is part of the national and European transport policy. Overview of national and EU studies, strategies and legislative plans enable to specify changes taking place in the EU aviation policy, as well as to create potential scenarios of its development with particular attention to the innovation of aerodromes and airports. Based on the above analysis it should be noted, that aims of the European institutions and agencies are: reduction amount of restrictive rules on general aviation (including GA aerodromes), spread concepts of multimodality and Small Aircraft Transport Systems, enhance competitiveness of the EU aviation sector but also reduction investment funding at airports. Conclusions may be a theoretical inspiration in the process of updating master plans of aerodromes and airports.